TEKNIK SELF MANAGEMENT UNTUK MENINGKATKAN KEMANDIRIAN BELAJAR SISWA MTS - Wahyaningrum, Andri; Muslim, Mudaris; Hidayat, Rian Rokhmad (Consilium: Jurnal Program Studi Bimbingan dan Konseling, 2017)
The purposes of this study were to determine the effectiveness of the implementation of group guidance and counseling services through self management to improve independent learning eighth graders student in MTs. This study is an experimental research with Treatment by Subjects Designs. Sampling technique using simple random sampling. Subjects in this study amounted to 112 students of class VIII. The instrument of data collection using Likert scale learning independence. Analysis of data using t test techniques. Results t test showed that value of tcount=26,941 and ttable=2,042, so tcount>ttable. Result of the research that self management with group guidance effective to improve independent learning student. Suggestion based on the result of research is that it is necessary to apply self management technique on group guidance implementation in MTs in order to be able to encourage the development of student learning independence.